Pembelajaran Inklusif Berbasis Multiple Intelligences: Upaya Memfasilitasi Keragaman Gaya Belajar Siswa Sekolah Dasar - Novita, Dewi; Herlina, Shella; Novita Sari, Galuh; Sayekti, Ika Candra (Universitas Muhammadiyah Surakarta, 2025)
This study aims to examine the implementation of inclusive learning based on multiple intelligences at MIM PK Kartasura as an effort to facilitate the diversity of students' learning styles and improve learning outcomes. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The data in this study is analyzed using data reduction, data display, and conclusion drawing techniques. The results show that the school has implemented student learning style mapping from the beginning of admission through readiness tests and Multiple Intelligences Research (MIR). The implementation of learning is done by grouping students into classes according to their intelligence tendencies, such as kinesthetic classes, linguistic, tahfidz, and SME (Science, Math, English). This strategy has proven effective in increasing motivation, understanding, and student achievement, while also providing space for Children with Special Needs (ABK) through special teacher assistance. Besides improving academic achievement, this model also contributes to character development, self-confidence, and student tolerance attitudes. In conclusion, inclusive learning based on multiple intelligences effectively creates a fair, friendly, and meaningful learning environment. This study recommends broader application of this model in other schools to support quality and equitable education.